Development of Radiofrequency Ablation Generator and Balloon-Based Catheter for Microendoluminal Thin-Layer Ablation Therapy Using the Rat Duodenum as a Model of Low-Impedance Tissue. (24th September 2021) - Nociarova, Jana; Novak, Marek; Polak, Jan; Hrudka, Jan; Porubsky, Stefan; Koc, Michal; Rosina, Jozef; Grebenyuk, Aleksandr N.; Sery, Radek; Gurlich, Robert; Hajer, Jan
Abstract : Radiofrequency ablation (RFA) is a routinely used, safe, and effective method for the tissue destruction. Often, in case of its application in malignant conditions, the extent of tissue destruction is insufficient due to the size of the target lesion, as well as due to the risk of heat-induced damage to the surrounding organs. Nevertheless, there are conditions requiring superficial precise-depth ablation with preservation of deeper layers. These are represented, for example, by mucosal resurfacing in case of Barrett's esophagus or treatment of recurrent mucosal bleeding in case of chronic radiation proctitis. Recently, new indications for intraluminal RFA use emerged, especially in the pancreatobiliary tract. In the case of intraductal use of RFA (e.g., biliary and pancreatic tract), there are currently available rigid and needle tip catheters. An expandable balloon-based RFA catheter suitable for use in such small-diameter tubular organs could be of benefit due to possible increase of contact between the probe and the target tissue; however, to prevent excessive tissue damage, a compatible generator suitable for low-impedance catheter/tissue is essential. This project aimed to develop a radiofrequency ablation generator and bipolar balloon-based catheter optimized for the application in the conditions of low-impedance tissue and (micro)endoluminal environment. Subsequent evaluation of biological effect in vivo was performed using duodenal mucosa in Wistar rat representing conditions of endoluminal radiofrequency ablation of low-impedance tissue. Experiments confirming the safety and feasibility of RFA with our prototype devices were conducted.